PARALINGUISTIC ISSUES IN CROSS-CULTURAL COMMUNICATION: BODY LANGUAGE - Xudayberganova Zebiniso; Jalolova G.M (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article examines the role of body language in cross-cultural communication, focusing on paralinguistic features such as gestures, posture, facial expressions, eye contact, and proxemics. The study highlights how differences in non verbal behavior can lead to misunderstanding between cultures and emphasizes the importance of cultural awareness for successful intercultural communication. The findings indicate that body language varies significantly across cultures and must be interpreted within its cultural context to avoid miscommunication.